BPK AND BPKP IN DETERMINING STATE FINANCE LOSS IN ORDER TO GAIN ANTI-CORRUPTION LAW EFFICIENCY OF ANTI-CORRUPTION LAW - Gabrielia Febrianty Shofiana (Perspektif, 2016)
Corruption case in Indonesia has been growing rapidly, therefore it needs big efforts to eradicate and prevent corruption, such as establishment of Corruption Eradication Commission (KPK) and the enactment of Law No. 31 Year 1999 as amended by Law No. 20 Year 2001 (Anti-Corruption Law). Corruption itself, as regulated in Article 2 and 3 Anti-Corruption Law, consists of some main elementswhose subject is anyone.The illegal act must exist which aims to enrich themselves and should create loss of state finance or economy. The efficiency of Anti-Corruption Law can be seen by how every article can be fully and properly fulfilled. Only authorized legal entities can determine state finance loss as one of corruption elements. Then, the problems emerge from the legal entity which actually has authority to determine state finance loss, yet if the fulfillment element of state finance loss is not discovered, it means that the corruption suspected cannot be charged. Supreme Audit Board (BPK/SAB) and Finance & Development Supervisory Board (BPKP/FDSB) are legal entities which have authority to conduct audit investigation. This study, by using normative-empirical research method, will discuss whether both or only one of those state agencies have authority to determine state finance loss.